A model for the aberrant DNA methylomes in aging cells and cancer cells. (18th July 2019) - Zhang, Huiming; Zhang, Kang; Zhu, Jian-Kang
Abstract: DNA methylation at the fifth position of cytosine is a major epigenetic mark conserved in plants and mammals. Genome-wide DNA methylation patterns are dynamically controlled by integrated activities of establishment, maintenance, and removal. In both plants and mammals, a pattern of global DNA hypomethylation coupled with increased methylation levels at some specific genomic regions arises at specific developmental stages and in certain abnormal cells, such as mammalian aging cells and cancer cells as well as some plant epigenetic mutants. Here we provide an overview of this distinct DNA methylation pattern in mammals and plants, and propose that a methylstat, which is a cis -element responsive to both DNA methylation and active demethylation activities and controlling the transcriptional activity of a key DNA methylation regulator, can help to explain the enigmatic DNA methylation patterns in aging cells and cancer cells.